Sir Ronald Syme and archeology - Arce, Javier (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
In his book The Roman Revolution, Sir Ronald Syme relied little on archaeological evidence. But this does not mean he disregarded it or that he considered archaeology unimportant to the writing of history. However, he did think that archaeology was not necessary, because texts, documentary evidence were the main sources for the historian. Many monuments and archaeological remains demonstrate, however, that History is incomplete when they are not taken into consideration.